Essential Readings in Problem-Based Learning : Exploring and Extending the Legacy of Howard S. Barrows - Walker, Andrew (Andrew Elbert) (Book collections on Project MUSE., 2015)
This book surveys the state of problem-based learning and assesses the impact of this innovative educational methodology on teaching and research effectiveness across a range of disciplines and in a variety of organizational contexts.